2013
DOI: 10.1007/s11244-013-0133-z
|View full text |Cite
|
Sign up to set email alerts
|

The Denitridation of Nitrides of Iron, Cobalt and Rhenium Under Hydrogen

Abstract: The denitridation behaviour of binary iron, cobalt and rehnium nitrides under H 2 /Ar has been investigated. The iron nitride was found to lose over 70 % of its as prepared nitrogen content at 400°C. The cobalt nitride was completely denitrided at 250°C. Rhenium nitride lost close to 90 % of its nitrogen at 350°C. In addition, Co-Re 4 prepared by ammonolyis was investigated, whilst only traces of NH 3 were lost from this material under H 2 /Ar at 400°C, with H 2 /N 2 it proved to be an active ambient pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…Reduction of ReN x to Re at 400 8 8Ca nd above can be explained by the instability of rhenium nitrides,e ven if ammonia is used here as ac o-reactant. Interestingly Alexander et al [27] have shown Re 3 Nt ol ose close to 90 % of its nitrogen under H 2 atmosphere at 350 8 8C. That is close to the deposition temperature (400 8 8C) where the ALD growth of Re begins instead of ReN x (Figure 1b).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Reduction of ReN x to Re at 400 8 8Ca nd above can be explained by the instability of rhenium nitrides,e ven if ammonia is used here as ac o-reactant. Interestingly Alexander et al [27] have shown Re 3 Nt ol ose close to 90 % of its nitrogen under H 2 atmosphere at 350 8 8C. That is close to the deposition temperature (400 8 8C) where the ALD growth of Re begins instead of ReN x (Figure 1b).…”
supporting
confidence: 54%
“…Interestingly Alexander et al [27] have shown Re 3 Nt ol ose close to 90 % of its nitrogen under H 2 atmosphere at 350 8 8C. Interestingly Alexander et al [27] have shown Re 3 Nt ol ose close to 90 % of its nitrogen under H 2 atmosphere at 350 8 8C.…”
mentioning
confidence: 98%
“…Within the literature, active CoRe 4 catalysts have been prepared by pre-treatment of their precursors with NH 3 [8,9]. However, as discussed by Wise and Markel in relation to the binary molybdenum nitride system, ammonolysis is not practical on a large scale for the preparation of nitrides from oxide precursors [13].…”
Section: Resultsmentioning
confidence: 99%
“…Attention has also centred upon Re based catalysts, with bulk Re modified with Co (in the atomic ratio 4:1 Re:Co, hereafter referred to as CoRe 4 ) having been reported to be particularly active [8]. In the case of catalysts comprising of Re alone, a marked degree of deactivation with time on stream was evidenced which has been attributed to decomposition of the active nitride phase to a mixture of rhenium nitride and rhenium metal [8,9]. The high activity of CoRe 4 has been attributed to stabilisation of a nitride phase [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of ReN x to Re at 400 °C and above can be explained by the instability of rhenium nitrides, even if ammonia is used here as a co‐reactant. Interestingly Alexander et al . have shown Re 3 N to lose close to 90 % of its nitrogen under H 2 atmosphere at 350 °C.…”
Section: Figurementioning
confidence: 99%